Chromogranin A is a reliable serum diagnostic biomarker for pancreatic neuroendocrine tumors but not for insulinomas - Qiao, Xin-Wei (BioMed Central, 2014)
BACKGROUND: Pancreatic neuroendocrine tumors (PNETs) are a group of rare tumors. Chromogranin A (CgA) was considered as the most practical and useful serum tumor marker in PNET patients. But peripheral blood levels of CgA are not routinely tested in Chinese patients with PNETs. This study was to assess the diagnostic value of CgA in Chinese patients with PNETs especially in patients with insulinomas. METHODS: Eighty-nine patients with PNETs including 57 insulinomas and 32 non-insulinoma PNETs as well as 86 healthy participants were enrolled in this study between September 2003 and June 2013. Serum levels of CgA were measured by ELISA method. Expression of CgA protein was detected in 26 PNET tissues including 14 insulinomas by immunohistochemical staining. RESULTS: Serum levels of CgA in 89 PNET patients were significantly higher than that in healthy controls (P = 7.2 × 10(−9)). Serum levels of CgA in 57 patients with insulinomas (median 64.8 ng/ml, range 25–164) were slightly higher than the levels in healthy controls (median 53.4 ng/ml, range 39–94) but much lower than the levels in 32 patients with non-insulinoma PNETs (median 193 ng/ml, range 27–9021), P = 0.001. The serum CgA levels were reduced in 16 of 17 patients with insulinomas after tumor resection. ROC curve showed that CgA values at 60 ng/ml distinguished patients with insulinomas from healthy controls but its sensitivity and specificity were 66.7% and 73.3%, respectively. In contrast, CgA values at 74 ng/ml distinguished patients with non-insulinoma PNETs from healthy controls, and the sensitivity and specificity were 65.6% and 91.9%, respectively. Except for two insulinomas with negative staining of CgA, 12 insulinoma tissues showed positive staining of CgA. CONCLUSION: CgA is a reliable serum diagnostic biomarker for PNETs but not for insulinomas.